Does prior contact with police reduce the likelihood of suicide? Examining the predictive ability of different incident types and the interaction effects - Walton, Darren (International journal of police science & management, 2017)
This study explores the relationship between prior contact with the police as a victim or person at risk and death by suicide. Findings from this study will improve our understanding of the role the police can have in preventing suicide. The sample comprised working age men who died suddenly in New Zealand during 2007-2011. Univariate and multivariate logistic regression models were used to assess the ability of age, ethnicity and prior police contact to predict whether the death was from suicide (n = 1140) or other causes (n = 7236). The analysis focused on prior police contact relating to: (1) threatened/attempted suicide, (2) domestic disputes and (3) potential mental health issues. Age, ethnicity and the three prior police contact types all independently predicted suicide. After controlling for demographic variables, prior police contact remained a predictor, with those relating to threatened/attempted suicide having the strongest predictive ability (Adjusted odds ratio [AOR] = 6.05, 4.75-7.70). Importantly, interaction effects were found between prior police contact types. The predictive ability of contact relating to threatened/attempted suicide reduced significantly if the person also had prior contact relating to a domestic dispute or potential mental health issue. Consistent with previous research, the main effects reported in this study suggest that the police have a role in suicide prevention. This study also makes a novel contribution by exploring the interaction effects between types of prior contact. Future research may investigate the interaction effects in more depth to reveal the contributing factors that reduce the odds of suicide.